IMMU-39. RNA LOADED LIPID-NANOPARTICLES FUNCTION AS CUSTOMIZABLE IMMUNOTHERAPEUTIC VEHICLES AGAINST MALIGNANT GLIOMAS. (11th November 2019) - Grippin, Adam; Wummer, Brandon; Mendez-Gomez, Hector; Stover, Brian; Huang, Jianping; Rinaldi, Carlos; Mitchell, Duane; Dobson, Jon; Sayour, Elias
Abstract: BACKGROUND: While dendritic cell (DC) vaccine therapy has shown considerable promise for glioblastoma (GBM) patients (Mitchell et al. Nature, 2015), their advancement into human clinical trials has been fraught with challenges in the development, manufacturing, and marketing of successful cancer immunotherapies. To circumvent the challenges associated with cell therapy, we have developed a new platform technology consisting of tumor derived mRNA complexed into lipid-nanoparticles (RNA-NPs) for systemic delivery to DCs in vivo and induction of antigen specific T cell immunity against GBM. OBJECTIVES/ METHODS: We sought to assess if surface and charge modifications to our custom lipid-NP could facilitate its localization to lymphoid organs and the brain tumor microenvironment. RESULTS: We demonstrate that intravenous administration of our unmodified custom RNA-NPs mediate systemic activation of DCs; these include activation of CD11c+ cells in the brains of animals with intact blood brain-barriers (BBBs). RNA-NPs mediate antigen specific T cell immunity and anti-tumor efficacy with increased tumor infiltrating lymphocytes against a NF-1/p53 mutant glioma that recapitulates features of human GBM in immunocompetent mice. Modification of surface charge could direct these RNA-NPs to lymphoid organs (e.g. spleen, lymph nodes) while modification of the lipid backbone (with cholesterol) enhances localization to innate immune cells in NF-1/p53 mutant and GL261 gliomas. We therefore assessed if this customizable lipid-NP could be leveraged for delivery of immune checkpoint inhibitors (ICIs) (i.e. PD-L1 siRNA) to the brain tumor microenvironment. Compared with scrambled siRNA-NPs in combination with ICIs, surface modified siRNA-NPs (antagonizing PD-L1) in combination with ICIs mediated significant antitumor efficacy with 37% long term survivors in an otherwise fatal brain tumor model. CONCLUSION: We designed multifunctional RNA-NPs with a simple, scalable synthesis method that enables delivery of nucleic acids to innate immune cells in lymphoid organs and brain tumors.